UPAYA MEMBENTUK KARAKTER ANAK MELALUI LOCAL WISDOM DALAM FESTIVAL GENERASI EMAS DI NAGORI BAH BIRONG ULU MANRIAH - Nabila Arrahma; Harun Al Rasyid (Jurnal Recoms, 2025)
The "Festival Generasi Emas" held in Nagori Bah Birong Ulu Manriah is a community-based character education initiative designed to address the challenges of character development in children in the digital era. This activity combines elements of entertainment, education, local culture, and religious values ​​through various competitions such as the call to prayer (adhan), memorization of short surahs (suras), coloring, and traditional games. The goal is to instill values ​​such as self-confidence, responsibility, cooperation, tolerance, and discipline naturally through enjoyable, hands-on experiences. The method used is a descriptive qualitative approach with observation, interviews, and documentation as data collection techniques. The results of the activity show, first, a significant positive impact on children's character development, such as increased empathy, social interaction, and enthusiasm for learning. Second, the festival also reduces dependence on gadgets and builds children's self-confidence. Third, this activity proves that character education can be carried out effectively through a creative, participatory, and local culture-based approach.